Exploring Domains and Elements for Students' Career Pathways in TVET through an Asset-Based Approach - Kamri, Khairol Anuar; Hasan, Azman; Mahdin, Hairulnizam; Kamaruddin, Yuslizar; Wan Ismail, Wan Ahmad Amir Zal (Journal of Technical Education and Training, 2025)
In the landscape of Technical and Vocational Education and Training (TVET), optimizing career development pathways for post-secondary school youth remains a critical issue. This research addresses the challenge by focusing on mapping the potential capital of youth. Youth capital mapping is an approach to systematically explore and document the realities of their potential and assets. The study employs the “Asset-Based Approach” theory, which emphasizes mapping the potential and resources possessed by youth. A combination of qualitative design through Focus Group Discussions (FGD) and semi-quantitative design using the Nominal Group Technique (NGT) was employed. A total of 10 informants from the TVET industry and field participated in both FGD and NGT sessions to achieve two primary objectives: to explore the domains and elements of the potential of post-secondary school youth for TVET career pathways, and to identify the domains and elements of their potential for TVET career pathways. The study identified two main assets influencing the potential of post-secondary school youth in building TVET career pathways: internal assets (interest, skills, values, and physical attributes) and external assets (environmental support and the workforce needs of local sectors). Special emphasis was placed on the role of digital assets, which have been underexplored in previous studies. Ownership of and proficiency in digital skills were found to be critical in enhancing youth employability and competitiveness in the era of the Fourth Industrial Revolution (IR 4.0). While other assets, such as social, economic, and physical support, are also important, digital assets require more focused attention in shaping future-ready skills and ensuring youth engagement in the rapidly growing TVET job sectors. Furthermore, a holistic approach to assessing student potential that encompassing interests, skills, and talents is needed to ensure more suitable and effective TVET career pathways.